Assessment of Neuroprotective Effects of Low-Intensity Transcranial Ultrasound Stimulation in a Parkinson’s Disease Rat Model by Fractional Anisotropy and Relaxation Time T2∗ Value - Dong, Yanchao; Liu, Defeng; Zhao, Yuemei; Yuan, Yi; Wang, Wenxi; Wu, Shuo; Liang, Xin; Wang, Zhanqiu; Liu, Lanxiang (Frontiers in Neuroscience, 2021)
Background: Low-intensity transcranial ultrasound (LITUS) may have a therapeutic effect on Parkinson's disease (PD) patients to some extent. Fractional anisotropy (FA) and relaxation time T2* that indicate the integrity of fiber tracts and iron concentrations in brain tissue have been used to evaluate the therapeutic effects of LITUS. Purpose: To use FA and T2* values to evaluate the therapeutic effects of LITUS in a PD rat model. Materials and methods: Twenty Sprague-Dawley rats were randomly divided into a hemi-PD group (n=10) and a LITUS group (n=10). Single-shot spin echo echo-planar imaging and fast low-angle shot T2WI sequences at 3.0T were used. The FA and T2* values on the right side of the substantia nigra (SN) pars compacta were measured to evaluate the therapeutic effect of LITUS in the rats. Results: One week after PD-like signs were induced in the rats, the FA value in the LITUS group was significantly larger compared to the PD group (0.214±0.027 vs. 0.340±0.032, t=2.864, P=0.011). At the 5th and 6th weeks, the FA values in the LITUS group were significantly smaller compared to the PD group (5th week: 0.290±0.037 vs. 0.405±0.027, t=2.385, P=0.030; 6th week: 0.299±0.021 vs. 0.525±0.028, t=6.620, P<0.0001). In the 5th and 6th weeks, the T2* values in the injected right SN of the LITUS group were significantly higher compared to the PD group (5th week, 12.169±0.826 in LITUS group vs. 7.550±0.824 in PD group; 6th week, 11.749±0.615 in the LITUS group vs. 7.550±0.849 in the PD group). Conclusion: LITUS had neuroprotective effects and can reduce the damage of 6-OHDA-induced neurotoxicity in hemi-PD rats. The combination of FA and T2* assessments can potentially serve as a new and effective method to evaluate the therapeutic effects of LITUS.